1973
DOI: 10.1002/hlca.19730560751
|View full text |Cite
|
Sign up to set email alerts
|

13C‐NMR. Spectra of Pteridines

Abstract: 13C-NMR. spectra of pterin, xanthopterin, isoxanthopterin, leucopterin, lumazinc and of the model compounds isocytosine and desamino-isocytosine have been measured as anions and cations in I M KaOD, CF&OOH, H,SO, and FSO,H solutions. The spectra were analysed by means of heteronuclear double resonance, with the aid of non-dccoupled spectra, and by spectral comparison. The results are interpreted in terms of the ionisation statc of the pteridines in the four solvents and are comparcd with those obtained from lK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

1974
1974
1998
1998

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…According to the nonsymmetric substitution pattern of the central pyrimidine, the 13 C NMR spectra of all compounds showed four quaternary carbon atoms of the pyrimidine moiety. In general, the C-5 resonances of 4(3 H )-pyrimidones are not significantly influenced in passing from the neutral to the anionic species . Likewise, the chemical shifts of the C-5 positions of the dications and the betaines are similar, whereas the resonances of the C-2 and C-6 atoms differ significantly [e.g., 11 : δ = 152.21, 152.77 ppm; 8a : δ = 150.82, 155.49 ppm].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the nonsymmetric substitution pattern of the central pyrimidine, the 13 C NMR spectra of all compounds showed four quaternary carbon atoms of the pyrimidine moiety. In general, the C-5 resonances of 4(3 H )-pyrimidones are not significantly influenced in passing from the neutral to the anionic species . Likewise, the chemical shifts of the C-5 positions of the dications and the betaines are similar, whereas the resonances of the C-2 and C-6 atoms differ significantly [e.g., 11 : δ = 152.21, 152.77 ppm; 8a : δ = 150.82, 155.49 ppm].…”
Section: Resultsmentioning
confidence: 99%
“…In continuation of our work on charge-cumulated and charge-separated pyrimidines, we chose the pyrimidin-4-olate moiety I , the anion of 4( 3H )-pyrimidone, as the target fragment of the desired heterocyclic tripoles. The delocalized negative charge is associated with a fragment that is isoconjugate with the benzyl anion II .…”
Section: Resultsmentioning
confidence: 99%
“…We have previously observed that an alkyl group at position 6 activates the reactive methyl group at the neighbouring positions in 1 and 5, whereas more distant methyl groups are substantially deactivating, as shown, for example, by the mutua1 deactivating effects of the 5-and 7-methyl groups in 5 (R = R' = CH,) (6,7).…”
Section: Introductionmentioning
confidence: 95%
“…Although the general base catalyzed reaction is thus disqualified from consideration in this respect, the general acid catalyzed reaction is not. This is because protonation occurs at N-8 in 2 (7), and at N-1 in 1,' which produces identical cations except for the substitution of hydrogen for methyl at N-8 (eqs.…”
Section: Introductionmentioning
confidence: 99%
“…*H Chemical Shifts0 of Nicotinic Acid and Its Charged Species (C = 0.148 M) 20:80 (v/v)5 values in ppm from DSS as internal reference.…”
mentioning
confidence: 99%